Correlative 3D SBFSEM data from: Intermittent bulk release of human cytomegalovirus - Flomm, Felix; Soh, Timothy K; Schneider, Carola; Wedemann, Linda; Britt, Hannah M; Thalassinos, Konstantinos; Pfitzner, Soeren; Reimer, Rudolph; Grünewald, Kay; Bosse, Jens Bernhard (Dryad, 2022)
Human Cytomegalovirus (HCMV) can infect a variety of cell types by using
virions of varying glycoprotein compositions. It is still unclear how this
diversity is generated, but spatio-temporally separated envelopment and
egress pathways might play a role. So far, one egress pathway has been
described in which HCMV particles are individually enveloped into small
vesicles and are subsequently exocytosed continuously. However, some
studies have also found enveloped virus particles inside multivesicular
structures but could not link them to productive egress or degradation
pathways.We used a novel 3D-CLEM workflow allowing us to investigate these
structures in HCMV morphogenesis and egress at high spatio-temporal
resolution. We found that multiple envelopment events occurred at
individual vesicles leading to multiviral bodies (MViBs), which
subsequently traversed the cytoplasm to release virions as intermittent
bulk pulses at the plasma membrane to form extracellular virus
accumulations (EVAs). Our data support the existence of a novel bona fide
HCMV egress pathway, which opens the gate to evaluate divergent egress
pathways in generating virion diversity.
Details on data acquisition and processing can be found in the original
publication. The uploaded here are the unprocessed raw data.
The data are in the proprietary dm4 format as saved by the acquisition
software. However, they can be easily opened and converted in Fiji/ImageJ
with the Bioformats importer. We recommend alignment of the stack and
binning of 2x2 for working with the data.
Keywords: FOS: Biological sciences; Assembly; Egress; CLEM; Serial Block-Face Scanning Electron Microscopy (SBFSEM); HCMV; Human cytomegalovirus; Microscopy